Antioxidants: Wonder drugs or quackery?. (18th September 2017) - Azzi, Angelo
Abstract: An answer to the question posed by the title must be simple not to disturb in his tomb Albert Einstein, who wrote "Man muß die Dinge so einfach wie möglich machen. Aber nicht einfacher". A simple answer (not simpler) can be: Antioxidants are not antioxidants, they are not wonder drugs and they are not all quackery; but they are not nothing. The arguments in support of this conundrumic statement will be developed below. © 2017 BioFactors, 43(6):785–788, 2017